2021
DOI: 10.3389/fmars.2021.682616
|View full text |Cite
|
Sign up to set email alerts
|

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus)

Abstract: Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 66 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…It is well known that plastic waste at sea is undergoing a process of fragmentation and miniaturization, so it is logical to expect that large quantities of MaP can generate corresponding quantities of MeP and MiP (Crawford and Quinn 2017;Chamas et al 2020). Similar studies have already identified positive relationships between MiP ingestion and MaP hotspots at the sea bottom (Alomar et al 2020;Franceschini et al 2021). Particles, however, increase their ability to be transported as they become smaller (Zhang 2017), and thus oceanographic factors can greatly affect the spread and accumulation of different sizes of plastic particles.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…It is well known that plastic waste at sea is undergoing a process of fragmentation and miniaturization, so it is logical to expect that large quantities of MaP can generate corresponding quantities of MeP and MiP (Crawford and Quinn 2017;Chamas et al 2020). Similar studies have already identified positive relationships between MiP ingestion and MaP hotspots at the sea bottom (Alomar et al 2020;Franceschini et al 2021). Particles, however, increase their ability to be transported as they become smaller (Zhang 2017), and thus oceanographic factors can greatly affect the spread and accumulation of different sizes of plastic particles.…”
Section: Discussionmentioning
confidence: 80%
“…The decreasing amount of plastics associated with the distance from the coast could be interpreted as the move away from the source of pollution. This variable was one of the major factors that negatively affect the amount of waste on the seabed along the coast (Coll et al 2012;Steer et al 2017;Sbrana et al 2020;Franceschini et al 2021). Accordingly, the coast of the Tyrrhenian Sea (GSA9) hosts a series of fishing grounds along a narrowed shelf that receives plastic waste through some important sources including the rivers Tiber and Arno (Inghilesi et al 2008;Ludwig et al 2009;Montuori et al 2016;Crosti et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The marine litter issue is raising concerns about both the impact of litter on marine ecosystems (Kühn et al, 2015) and the economic costs related to debris removal (Newman et al, 2015;Franceschini et al, 2021). Indeed, Marine Strategy Framework Directive (European Commission, 2008) (MSFD) has been implemented with the descriptor 10, where the European Commission has asserted that the marine litter represents one of the main disturbances of marine ecosystems, outlining evaluation criteria for this type of pollutants, such as to monitor their abundance, composition and danger to waters belonging to the Member States (Galgani et al, 2013a(Galgani et al, , 2013bCau et al, 2022).…”
Section: Introductionmentioning
confidence: 99%